Faire le ménage ensemble, prendre soin des lieux - Amélie Tehel (GéoProximitéS)
This short paper focuses on cleaning work within a shared space in Rennes (France) called the Hôtel Pasteur. Cleaning work is structurally an invisible and depreciated work. However, this paper shows that cleaning a shared space can also demonstrates a singular affective bond with the space and the community.